Mitos Good Influencer dan Politik citra Awkarin dalam Pusaran Demonstrasi Mahasiswa Menolak RKUHP - Khumaid Akhyat Sulkhan (Program Studi Ilmu Komunikasi, 2020)
This paper discusses how Awkarin reproduces the myth of good influencers as part of her political image in the student action against the RKUHP on September 24, 2019. With the semiotic method developed by Roland Barthes, the author examines the meaning of denotation and connotation in Awkarin's Instagram photos that record her involvement in the action at Senayan. As a result, the authors found that Awkarin built the image of an influencer who cares about social and political issues and mobilizes all their potential to help the public. However, the myth of the good influencer Awkarin is problematic, because she only involves herself in issues that are popular in society without going into further detail Keywords : Good Influencer, Politics of Image, Awkarin, Student Demonstration.